Mathematics for elementary school teachers : Explorations - Bassarear, Tom. (Boston : Houghton Mifflin, 2001)
This book is aboutFoundations for Learning mathematics; Fundamental Concepts; the Four Fundamental Operations of Arithmethic; Number theory; Extending the Number System; Proportional Reasoning; Uncertainty: Data and Chance; Geometry as Shape; Geometry as Transforming Shapes; and Geometry as Measurement.
Keywords: Mathematics; Mathematics -- Study and teaching (Primary)